Bears - Helbrough, Emma; Lawrence, Michelle Co-designer; Thompson, Joseph Co-designer; Kushii, Tetsuo Co-illustrator; Larkum, Adam Co-illustrator (New York : Scholastic, 2006)
What do bears eat? Where do they live? Can they swim? In this book you'll find the answers and lots more about the fascinating world of bears.
M
b
b